Chronic troponin elevation assessed by myocardial T1 mapping in patients with stable coronary artery disease. Issue 16 (21st April 2023) - Segre, Carlos Alexandre W.; de Lemos, James A.; Assunção Junior, Antonildes Nascimento; Nomura, Cesar Higa; Favarato, Desiderio; Strunz, Celia Maria Cassaro; Villa, Alexandre Volney; Parga Filho, Jose Rodrigues; Rezende, Paulo Cury; Hueb, Whady; Ramires, Jose Antonio Franchini; Kalil Filho, Roberto; et al.
Abstract : Background: Cardiac troponin detected with sensitive assays can be chronically elevated, in the absence of unstable coronary syndromes. In patients with chronic coronary artery disease, clinically silent ischemic episodes may cause chronic troponin release. T1 mapping is a cardiovascular magnetic resonance technique useful in quantitative cardiac tissue characterization. We selected patients with anatomically and functionally normal hearts to investigate associations between chronic troponin release and myocardial tissue characteristics assessed by T1 mapping. Methods: We investigated the relationship between cardiac troponin I concentrations and cardiovascular magnetic resonance T1 mapping parameters in patients with stable coronary artery disease enrolled in MASS V study before elective revascularization. Participants had no previous myocardial infarction, negative late gadolinium enhancement, normal left ventricular function, chamber dimensions and wall thickness. Results: A total of 56 patients were analyzed in troponin tertiles: nativeT1 and extracellular volume (ECV) values (expressed as means ± standard deviations) increased across tertiles: nativeT1 (1006 ± 27 ms vs 1016 ± 27 ms vs 1034 ± 37 ms, ptrend = 0.006) and ECV (22 ± 3% vs 23 ± 1.9% vs 25 ± 3%, ptrend = 0.007). Cardiac troponin I concentrations correlated with native T1( R = 0.33, P = .012) and ECV ( R = 0.3, P = .025), and were independently associated with nativeT1 ( P = .049) and ventricular mass index ( P = .041) in multivariable analysis. Conclusion: In patients with chronic coronary artery disease and structurally normal hearts, troponin I concentrations correlated with T1 mapping parameters, suggesting that diffuse edema or fibrosis scattered in normal myocardium might be associated with chronic troponin release.